New technologies in the Physical Education class. A positive experience with the digital video recording and vertical jump - Daniel Rojano Ortega (FEADEF, 2010)
The objective of the Basic Competences is to highlight the essential learning of the Secondary School Curriculum. The fourth Basic Competence introduces in the Secondary School Program the use of the Information and Communication Technologies as an essential element to be informed, to learn and to communicate. To that effect, this article tries to bring the new technologies to the Physical Education Class, specifically to the analysis of the vertical jump. This jump has been traditionally evaluated with the Sargent's test but this test has some errors which derive from the measuring process. Nowadays there are new very precise instruments often used in sports for the analysis of the vertical jump, but their high prices make it difficult to introduce them in the school. With this article we want to show that the digital video recording and the video edition programs constitute a very appropriate way to evaluate the vertical jump because it causes in the students great interest and implication.